Assessment of 3D-printed flexible antenna for microwave breast imaging - Guida, G.; Felício, J. M.; Costa, J. R.; Martins, R. A.; Fernandes, C. A.; Occhiuzzi, C. (2023 IEEE Conference on Antenna Measurements and Applications (CAMA), 2023)
Over the past few years, Microwave Imaging (MWI) has emerged as a potential alternative to conventional primary screening methods for breast cancer detection. Specifically, it could viably complement mammographic examinations, addressing the well-known drawbacks associated with the use of ionizing radiation. MWI techniques are non-invasive, relatively inexpensive, fast, and safe. All these characteristics make it ideal as a mass screening for early cancer detection.The present paper presents a numerical study aimed at investigating the performance of a flexible antenna with a 3D-printed Thermoplastic Polyurethane (TPU) substrate. Furthermore, after deploying these antennas within an array, the study explores the impact of polarization diversity on the imaging results. Specifically, the design consists of several antipodal Vivaldi antennas arranged around the anthropomorphic breast model in a circular configuration and in different orientations. The images reconstructed through radar-based imaging methods using reflection parameters collected from numerical simulations were compared to assess the impact of polarization diversity and show the detection of the tumor.